Efektifitas berbagai probiotik kemasan terhadap pertumbuhan dan produksi Burung Puyuh (Coturnix coturnix japonica) - Herlinae Herlinae; Yemima Yemima (Fakultas Peternakan Universitas Kristen Palangka Raya, 2016)
The research objective was to determine the effectiveness of various probiotics product on the growth and egg production of quail (Coturnix coturnix japonica). The study used Completely Randomized Design (CRD) with 4 treatment 5 replicates. The results showed that use of various probiotics product very significant effect on feed intake at fifth week. The use of various probiotics product effectively improve body weight gain at first week and fifth week. The efficiency of feed use is indicated on feed use of probiotics at fifth week. Various probiotics product effective in improving hen day up 66.43 to 67.62% compared with no probiotics. Key words : Quail, probiotics, growth, production.